Ironically unwell: anaemia and iron deficiency among health-aware adults in the UK - Irvine, Allister; Watt, Joanne; Kurth, Mary Jo; Lamont, John V.; Dowey, Le Roy; Fitzgerald, Peter; Niblock, Aaron; Fairweather, Alex; Ruddock, Mark W. (Frontiers in Nutrition, 2025)
BackgroundAnaemia and iron deficiency are a global healthcare burden affecting almost 25% of the population. Many anaemia cases are caused by depletion of iron stores which can be treated by oral iron supplementation. However, anaemia may also result from functional iron deficiency, where chronic inflammation prevents utilisation of stored iron. Anaemia and iron deficiency are rarely profiled in general populations; however, they can have significant healthcare implications.MethodsData from n = 33,029 serum samples were retrospectively analysed from individuals undertaking private health checks within Randox Health (UK). Samples were measured to detect anaemia, iron and vitamin deficiencies, based on established guidelines.ResultsThe overall prevalence of anaemia in the study was 6.0% (n = 1,917/31,803). The prevalence of anaemia was higher in females, with almost 1 in 10 (9.9%; n = 1,558/15,715) classified as anaemic; anaemia prevalence was highest in females aged 18–50 years. Similarly, absolute iron deficiency was also higher in females, with almost 1 in 3 (31.6%; n = 4,633/14,677) impacted. Functional iron deficiency was high in the study individuals across all age groups and sexes.ConclusionThe study identified that anaemia and iron deficiency are common underlying conditions in a health-conscious UK population. Despite the high prevalence of anaemia and iron deficiency burden on females of menstruating age, demonstrated in this study, and reported in the literature, screening for these conditions is not widespread. Should there be a national screening programme for anaemia and iron deficiency in females?